2017
DOI: 10.3233/jpd-160912
|View full text |Cite
|
Sign up to set email alerts
|

Regular Exercise, Quality of Life, and Mobility in Parkinson’s Disease: A Longitudinal Analysis of National Parkinson Foundation Quality Improvement Initiative Data

Abstract: Background Research-based exercise interventions improve health-related quality of life (HRQL) and mobility in people with Parkinson’s disease (PD). Objective To examine whether exercise habits were associated with changes in HRQL and mobility over two years. Methods We identified a cohort of National Parkinson Foundation Quality Improvement Initiative (NPF-QII) participants with three visits. HRQL and mobility were measured with the Parkinson’s Disease Questionnaire (PDQ-39) and Timed Up and Go (TUG). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
87
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 28 publications
(48 reference statements)
12
87
0
2
Order By: Relevance
“…A small study of 51 mild‐to‐moderate non‐demented PD patients randomised to either progressive resistance training or Modified Fitness Counts reported that both treatment modalities improved attention and working memory . The National Parkinson Foundation QII registry study also found that patients with PD who regularly exercised >150 min/wk had less cognitive decline at 12‐month follow‐up . Further research into the long‐term cognitive benefits of exercise therapy in PD is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A small study of 51 mild‐to‐moderate non‐demented PD patients randomised to either progressive resistance training or Modified Fitness Counts reported that both treatment modalities improved attention and working memory . The National Parkinson Foundation QII registry study also found that patients with PD who regularly exercised >150 min/wk had less cognitive decline at 12‐month follow‐up . Further research into the long‐term cognitive benefits of exercise therapy in PD is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…19 The National Parkinson Foundation QII registry study also found that patients with PD who regularly exercised >150 min/wk had less cognitive decline at 12-month follow-up. 2 Further research into the long-term cognitive benefits of exercise therapy in PD is warranted.…”
Section: E99mentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity is another important lifestyle factor that may affect PD onset, severity and progression. High levels of exercise in midlife are associated with lower PD risk, better disease prognosis and lower rates of serious complications [61]. A large international multicenter cohort study on early PD patients showed that higher self-reported activity scores were associated with younger age and male gender.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…At the other end of the disease spectrum, regular physical activity seems to particularly enhance quality of life in those with advanced disease, therefore studies testing exercise/physical activity interventions targeting this population are urgently required. As well as investigating high‐intensity exercise, trials aiming to increase routine daily physical activity and reduce sedentary behavior are on the horizon and may be more acceptable to some people with PD.…”
Section: The Next 10 Yearsmentioning
confidence: 99%